A germline FLT3 variant in aplastic anemia - Lemchukwu C. Amaeshi; Amalia A. Sofianidi; Aditi Shastri; Mendel Goldfinger; Marina Konopleva; Amit K. Verma; Mark Chaitowitz; Ioannis Mantzaris (Biomarker Research)
Abstract FMS-like tyrosine kinase 3 (FLT3) genetic variants are commonly seen in high-grade myeloid neoplasms and are typically gain-of-function mutations associated with a proliferative disease phenotype. Inactivating FLT3 variants have been less frequently described in non-malignant, autoimmune disorders and are uncommon in aplastic anemia (AA). Herein, we report the first to our knowledge, and unusual case of a germline, gain-of-function, FLT3 variant in a patient with severe AA treated successfully with immunosuppressive therapy. Although a proposed link between dysregulated FLT3 signaling and autoimmunity has been described and could be speculated in the case of AA, it is currently unknown whether a pathogenetic connection between an activating germline FLT3 variant and AA truly exists and whether the mutation signifies a lifelong risk of disease recurrence and/or clonal evolution. However, the recognition of the FLT3 gene as subject not only to somatic but also germline mutations is the first step in interrogating its functional implications. Further study of unusual genotype-phenotype combinations, such as in the case presented, may shed light on a potential pathogenetic link.